2012
DOI: 10.1101/cshperspect.a013680
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicle Pools and Dynamics

Abstract: Synaptic vesicles release neurotransmitter at chemical synapses, thus initiating the flow of information in neural networks. To achieve this, vesicles undergo a dynamic cycle of fusion and retrieval to maintain the structural and functional integrity of the presynaptic terminals in which they reside. Moreover, compelling evidence indicates these vesicles differ in their availability for release and mobilization in response to stimuli, prompting classification into at least three different functional pools. Ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
223
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(230 citation statements)
references
References 147 publications
(216 reference statements)
7
223
0
Order By: Relevance
“…In accordance with the restoration of gene expression changes, microglial elimination and repopulation restored age‐related reductions in neuronal complexities to those found in the young brain, while also modulating dendritic spine densities. Crucially, actin cytoskeleton remodeling is highly associated with synaptic plasticity and memory (Lamprecht, 2014), as is synaptic vesicle release (Alabi & Tsien, 2012), and we found that microglial replacement fully restores LTP, the synaptic mechanism underlying memory formation, in 24‐month‐old mice to levels comparable to 4‐month‐old mice.…”
Section: Discussionsupporting
confidence: 54%
“…In accordance with the restoration of gene expression changes, microglial elimination and repopulation restored age‐related reductions in neuronal complexities to those found in the young brain, while also modulating dendritic spine densities. Crucially, actin cytoskeleton remodeling is highly associated with synaptic plasticity and memory (Lamprecht, 2014), as is synaptic vesicle release (Alabi & Tsien, 2012), and we found that microglial replacement fully restores LTP, the synaptic mechanism underlying memory formation, in 24‐month‐old mice to levels comparable to 4‐month‐old mice.…”
Section: Discussionsupporting
confidence: 54%
“…The presynaptic terminal is characterized by a cluster of neurotransmitter-containing synaptic vesicles and transmission proceeds with their activity-driven fusion leading to the discharge of chemical transmitter towards postsynaptic receptors. While vesicles appear morphologically equivalent they can be sub-divided into pools on the basis of their functional behaviour, including a recycling pool (see 2,3 , readilyreleasable pool 4 , spontaneous pool 5,6 and superpool 7,8 . Understanding the properties of these pools has become increasingly important with the realization that they are potentially critical substrates in setting synaptic strength 9,10 and represent modifiable targets on which forms of plasticity 9,[11][12][13][14] or disease-like conditions [15][16][17] might act to modulate or disrupt information flow.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vesicles in recycling is a critical determinant of synaptic transmission (1,(13)(14)(15). However, it has never been rigorously determined how fast recently recaptured vesicles are organized to recycle and whether vesicles in the RP are homogeneously ready for use (25).…”
mentioning
confidence: 99%
“…The resting pool serves as a depot of vesicles for backup use (16,22). However, it has been debated for a decade whether nerve terminals use the majority (∼100%, from electrophysiology) or only a small fraction (5-40%, from fluorescence imaging and EM) of vesicles in recycling, and whether the RP size undergoes dynamic changes during varied neuronal activity (6,7,(23)(24)(25)(26)(27)(28).The use of vesicles in recycling is a critical determinant of synaptic transmission (1,(13)(14)(15). However, it has never been rigorously determined how fast recently recaptured vesicles are organized to recycle and whether vesicles in the RP are homogeneously ready for use (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation